Pretreatment of mosquito larvae with ultraviolet-B and nitropolycyclic aromatic hydrocarbons induces increased sensitivity to permethrin toxicity. Issue 10 (October 2022) - Ramkumar, Govindaraju; Muthusamy, Ranganathan; Narayanan, Mathiyazhagan; Dhanapal, Rajendran; Karthik, Chinnannan; Shivakumar, M.S.; Malathi, Govindhan; Kariyanna, B.
Abstract: Nitropolycyclic aromatic hydrocarbons (Nitro-PAH) are highly toxic PHA derivatives. Nitro-PHAs are emitted by carbonaceous materials and PHA post-emission transformation, which causes water and environmental pollution and also exists as carcinogenic and immunotoxic agents. UV light has been shown to cause DNA damage and improves the covalent binding of PAH to DNA significantly. Mosquito breeding grounds are pools of water that can be large open zones or encased ponds with varying levels of sunlight exposure. This research was performed to assess the combined effects of UV-B exposure and Nitro-PAH on the physiological function of Culex quinquefasciatus larvae. To assess the impact of UV-B irradiation and Nitro-PAH exposure on mosquito vectors, parameters were examined: (1) Nitro-PAH availability and its impact on cell fatalities; (2) the detoxifying abilities of cytochrome P450, glutathione-S-transferase, and esterase; (3) the reactions to Reactive Oxygen Species; and (4) The resistance of mosquito larvae to three synthetic pesticides (temephos, imidacloprid, and permethrin). UV-B and Nitro-PAH treatment caused cellular damage and increased major detoxification enzymes such as α & β-esterase, cytoP450, CAT, GST, and POX. The levels of oxidative stress, ROS and protein carbonyl content, nitrite, ascorbic acid and thiobarbituric acid were decreased significantly. Toxicology bioassays revealed that UV-B + Nitro-PAH exposure significantly increased larval susceptibility. The current study concludes that prior exposure to Nitro-PAHs and UV-B may make mosquito larvae more vulnerable to chemical insecticides. Abstract : Control; Nitro-PAH; Mosquito; Permethrin; Detoxification enzymes; ROS; Culex quinquefasciatus .